2009
DOI: 10.1021/om9001022
|View full text |Cite
|
Sign up to set email alerts
|

Ring-Functionalized Molybdenocene Complexes

Abstract: The synthesis and characterization of new ring-functionalized molybdenocene derivatives [CpCp′Mo(CO) 2 ] 2+ and [CpCp′Mo(CO)Br] + (η 5 -C 5 H 4 R; R ) CH 2 CH 2 OMe, CH 2 CH 2 COOEt, CH 2 CH 2 OOCMe, COOMe) are reported. Three alternative routes were used to assemble the CpCp′Mo moiety. Following route I, the unsubstituted precursor [CpMo(CO) 2 (NCMe) 2 ] + reacts with substituted cyclopentadienes (Cp′H) to give after oxidation dicationic compounds [CpCp′Mo(CO) 2 ] 2+ . Alternatively, route II introduces the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…We have previously observed that the attachment of only one COOMe group at the Cp ligand does not influence the reaction path. 16 The herereported unexpected switch of the reactivity can be explained by much higher affinity of the functional groups in the cyclopentadienyl toward protonation. The second electronwithdrawing group crosses the borderline between attack of the allyl and cyclopentadienyl ligands.…”
Section: ■ Conclusionmentioning
confidence: 77%
See 3 more Smart Citations
“…We have previously observed that the attachment of only one COOMe group at the Cp ligand does not influence the reaction path. 16 The herereported unexpected switch of the reactivity can be explained by much higher affinity of the functional groups in the cyclopentadienyl toward protonation. The second electronwithdrawing group crosses the borderline between attack of the allyl and cyclopentadienyl ligands.…”
Section: ■ Conclusionmentioning
confidence: 77%
“…C 5 H 4 COOMe). 16 In the case of compounds 6 and 7, we observe a very different product. Reaction with HBF 4 in the solution containing acetonitrile gives cationic allyl compound [(η 3 -C 3 H 5 )Mo(CO) 2 (NCMe) 3 ][BF 4 ] (11) as the sole product; see Scheme 4.…”
Section: ■ Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…The structural parameters, describing the coordination sphere of molybdenum, are in line with data of structurally related cyclopentadienyl and indenyl compounds described previously. 13,14,[44][45][46] The reaction of 2 with lower than stoichiometric amount of bpy or phen gives a material insoluble in common organic solvents that strongly contrasts with properties of the starting compounds as well as the products 4a and 5a. Elemental analysis of the products together with their insolubility suggests an appearance of the ionic pair consisting of a large complex cation and a large complex anion [(h 5 -4,7-Me 2 C 9 H 5 )Mo(CO) 2 ( N,N L)] [(h 5 -4,7-Me 2 C 9 H 5 )Mo(CO) 2 Cl 2 ] (4b-9: N,N L ¼ bpy, 5b-9: N,N L ¼ phen), see Scheme 5.…”
Section: Resultsmentioning
confidence: 99%